The role of human resources management in assessing employee performance – An applied study on a sample from the colleges of King Khalid University – - Abd Al-Khair, Asia Yagoub Alhadi (Journal of Economic, Administrative and Legal Sciences, 2021)
The paper examined the role of human resources management in the process of evaluating the performance of employees applying to King Khalid University in the period (2016- 2019). The problem of the paper is an attempt to know the role of human resources management in the process of evaluating the performance of the university. The study aimed to highlight the role that human resources management plays in the evaluation process The performance of workers, which is reflected in the course on achieving the goals of the university, as well as aimed at identifying the obstacles facing human resources management in carrying out the performance evaluation process, which limits its effectiveness. The paper followed the descriptive analytical approach, the most important results of the paper. The Human Resources Department works to raise the efficiency of workers through attention to training programs that help in continuous growth and improvement. The university relies on the information provided by the performance appraisal system for the purpose of determining the rewards and incentives that distinguished employees deserve. The most important recommendations of the paper should be the process of evaluating the performance of university employees in the great interest, the need to benefit from feedback in the process of performance evaluation in dealing with the deficiencies in performance.